A phase I open label dose‐escalation study to evaluate the tolerability, safety and immunological efficacy of sub‐urothelial durvalumab injection in adults with muscle‐invasive or high‐risk non‐muscle‐invasive bladder cancer (SUBDUE‐1, SUB‐urothelial DUrvalumab injection‐1 study): clinical trial protocol. Issue Volume 128:Issue Supplement 1(2021) (6th May 2021) - Moe, Andrew; Liow, Elizabeth; Redfern, Andrew; Swarbrick, Nicole; Ferguson, Tom; Davis, Ian D.; Hayne, Dickon
Abstract : Objectives: This article presents the clinical trial protocol for a phase I open label dose‐escalation study to evaluate the tolerability, safety and immunological efficacy of sub‐urothelial durvalumab injection in adults with muscle‐invasive or high‐risk non‐muscle‐invasive bladder cancer (NMIBC), the SUB‐urothelial DUrvalumab injection‐1 study (SUBDUE‐1). The primary objectives of this study are to assess the safety of sub‐urothelial injection of durvalumab using patient reported outcome measures and observed local or systemic adverse events. The secondary objectives are to examine the local immunological efficacy of sub‐urothelial administration of durvalumab. Patients and Methods: The SUBDUE‐1 trial will include adult patients with either high‐risk NMIBC or MIBC, who are scheduled for radical cystectomy or who have refused or are unsuitable for systemic neoadjuvant chemotherapy. Three fixed total dose levels of durvalumab (25, 75, 150 mg) will be studied to identify a dose suitable to be taken forward into phase II trials. The primary endpoint is to evaluate the safety and tolerability of the trial intervention in terms of the incidence and severity of adverse events and the potential establishment of dose‐limiting toxicities. The secondary efficacy endpoints include rates of pT0 status at resection, lymph node status, as well as the change in distribution of tumour‐infiltrating lymphocytes and tumour‐activated macrophages between pre‐ and post‐injection bladder biopsies. Translational studies will focus on bladder tumour molecular sub‐typing, immune infiltrate characterisation, and immune checkpoint protein expression relative to efficacy end‐points. Outcome and Significance: If proven safe and effective, this novel strategy comprising sub‐urothelial durvalumab injections aimed at promoting an anti‐tumour immune reaction, will provide additional treatment options for reducing tumour recurrence and progression in treatment‐naïve patients with high‐risk NMIBC or in patients with bacille Calmette–Guérin‐refractory NMIBC. Local administration of durvalumab may be associated with a reduced rate of immunological side‐effects and lower costs when compared to systemic delivery.